ELEMENTS OF NARRATIVE AND FUNCTION OF NARRATOR IN JUN CHIU’S CROP CIRCLES - Dini Oktavia; Rahmadsyah Rangkuti; Nuhammad Yusuf (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The purposes of this study are to find out the elements of narrative and the function of narrator in Jun Chiu’s silent comic Crop Circles. This research applied qualitative design. The data of this study were in the form of 20 pictures taken from the silent comic. The data were collected through stages: finding out and determining, classifying and separating the pictures conveying illustration of a narrative. The analysis of the data was done qualitatively by using the theory of phase analysis by Miles, Huberman and Saldana covering condensation, display and verification.  The research results show that the elements of narrative found in Jun Chiu’s comic pictures Crop Circles narrative mood (transposed speech-indirect style); narrative instance (narrative voice: heterodiegetic narrator, time of narration: simultaneous narration; narrative perspective: external focalization), narrative levels (embedded narrative, metalepsis) and narrative time (order: analepsis, narrative speed: ellipsis, frequency of events: singulative narration). The narrator carried ideological function because the narrator illustrates the pictures to introduce public policy.